Antibacterial Activity Of Nginang Herb Extract Mouthwash Formulation Against The Streptococcus Mutans Bacteria - Pradea Indah Lukito; Makhabbah Jamilatun; Innaya Rahma Salsabila (International Journal of Science and Environment (IJSE), 2024)
Nginang was chewing the raw green betel leaf combined with areca nut and gambier seeds, it was Indonesian people’s habit in ancient times to maintain the dental health. Over time, the nginang mixture was developed into a mouthwash formula to make it easier and acceptable to use. Mouthwash is a liquid form preparation with a pleasant taste and smell, to keep clean the mouth. The phytochemical content in the nginang herbs was tannin which is a phenolic compound. The mechanism of action of phenolics was by inactivated the microbial cell adhesion and to avoid the attached to host cells by the cell surface. The purpose of this study was to determine the antibacterial activity by inhibitory zones diameter of the formula of nginang herb mouthwash against Streptococcus mutans bacteria. This type of research was descriptive and quantitative with an experimental research design. The experimental research by making mouthwash formulations of nginang herb extract (green betel leaf, areca seed, and gambier) in three formulas with a concentration ratio of green betel leaf: areca nut: gambir, that were Formula 1(3%:3% :3%), Formula 2 (3%:2%:1%), and Formula 3 (3%:1%:2%), the quality of the formulas was carried out by physical quality parameters (organoleptic, pH, clarity, and viscosity), and the antibacterial activity against Streptococcus mutans. The results of this study of the three formulas were had liquid form, clear to browny color, and slightly smell like mint and extract, the pH at 5.4, and had a viscosity value about 0.79. The results of antibacterial activity against Streptococcus mutans study was indicated that the formula which contain of green betel leaf, areca seed, and gambier had very strong category based of the inhibitory zone.